Injury Mechanisms for Anterior Cruciate Ligament Injuries in Team Handball - Olsen, O. E.; Myklebust, G.; Engebretsen, L.; Bahr, R. (The American Journal of Sports Medicine, 2004)
Objective: To describe the mechanisms for anterior cruciate ligament injuries in female team handball. Study Design: Descriptive video analysis. Methods: Twenty videotapes of anterior cruciate ligament injuries from Norwegian or international competition were collected from 12 seasons (1988-2000). Three medical doctors and 3 national team coaches systematically analyzed these videos to describe the injury mechanisms and playing situations. In addition, 32 anterior cruciate ligament-injured players in the 3 upper divisions in Norwegian team handball were interviewed during the 1998-1999 season to compare the injury characteristics between player recall and the video analysis. Results: Two main injury mechanisms for anterior cruciate ligament injuries in team handball were identified. The most common (12 of 20 injuries), a plant-and-cut movement, occurred in every case with a forceful valgus and external or internal rotation with the knee close to full extension. The other main injury mechanism (4 of 20 injuries), a 1-legged jump shot landing, occurred with a forceful valgus and external rotation with the knee close to full extension. The results from the video analysis and questionnaire data were similar. Conclusions: The injury mechanism for anterior cruciate ligament injuries in female team handball appeared to be a forceful valgus collapse with the knee close to full extension combined with external or internal rotation of the tibia.